Analisis Kadar Timbal (Pb) pada Rambut Pekerja Bengkel Tambal Ban dan Ikan Mas di Sepanjang Jalan Soekarno-Hatta Bandar Lampung Secara Spektrofotometri Serapan Atom - Samsuar Samsuar; M Kanedi; Sherly Pebrice; Widhalita Ari P (Jurnal Kesehatan, 2017)
Lead is often referred to as a lead or of lead, the metal is denoted by Pb.Heavy metal lead can cause poisoning and accumulate in the human body.Process of entry into the body can lead through food and drink, the air and the penetration of the skin.Absorption through the skin may occur due to these compounds soluble in oils and fats.Lead through the air into the respiratory tract to be absorbed and binds to lung blood is then circulated to all the tissues and organs of the body, while by foods possible cause fish was foods source of protein had bepouled of lead.On the hair can be bound to sulfhydryl groups so that the lead content in the hair can be an indicator of lead contamination.This study aims to analyze the levels of lead in the hair tire repair shop workers and goldfish keep in along the Soekarno-Hatta Airport Lampung.Examination conducted quantitative analysis using Atomic Absorption Spectrophotometry.The determination of the concentration of lead in Atomic Absorption Spectrophotometry obtained linear regression equation of lead standard solution is y: 0.0100x - 0.00933, the correlation coefficient (rx,y) of 0.999.Lead provides maximum absorption at a wavelength of 283.3 nm.The results showed that the positive tire repair shop workers have polluted lead.The highest lead level is 4.813 ppm while the lowest lead content was 0.258 ppm. In fish gills and meat of goldfish the highest lead level ware 0.15878 and 0.1160 ppm while the lowest lead content ware 0.1136 and 0.0539 ppm.